Access to public information in the jurisprudence of the Constitutional Court and its impact in ordinary justice - Fernández González, Miguel Ángel (Derecho Público Iberoamericano, 2021)
The jurisprudence of the Constitutional Court is systematized (between June 2012 and January 2021) about the principle of publicity, contained in article 8, paragraph 2 of the Constitution, regarding the regulation provided for in Law No. 20.285, on access to public information, and its impact on the resolution of the respective pending claim in the Appeals and Supreme Courts.